A interface entre o subsistema cultural e o tráfico de pessoas / The interface between the cultural subsystem and human trafficking - Gebrim, Luciana Maibashi (Revista Direito e Práxis, 2016)
DOI: 10.12957/dep.2016.16417 Resumo O artigo pretende abordar a influência do subsistema cultural na elaboração de políticas criminais de enfrentamento ao tráfico de seres humanos. A partir de pesquisa bibliográfica e documental, objetiva-se demonstrar que elementos produzidos pelo subsistema cultural se comunicam com o subsistema penal, pressionando-o a dar resposta na forma de políticas criminais muitas vezes contrárias aos interesses das supostas vítimas. Palavras-chave: Discriminação de Gênero. Política Criminal. Tráfico de Pessoas. Abstract This article aims to address the influence of cultural subsystem on criminal policy-making to counter human trafficking. Considering a systemic constructivist approach, we start from the premise that human trafficking is a hipercomplex phenomenon, as a result of the combination of several elements, produced and reproduced on various social subsystems (economic, political, cultural, legal), which interact with each other. The goal is to demonstrate that the elements produced by the cultural subsystem, such as the moralism, patriarchy, gender discrimination and domestic violence, communicate with the criminal subsystem, pushing it to respond through criminal policies that go often against the alleged victims’ interests. Keywords: Gender Discrimination. Criminal Policy. Human Trafficking.